Management of Iatrogenic Ulnar Nerve Transection - Henry, Mark (Journal of Hand and Microsurgery, 2015)
A case of iatrogenic ulnar nerve laceration at the elbow is presented. Five subsequent surgeries over the course of the ensuing 20 months were performed to address this complication. The article examines the scientific basis for the various decisions needed to formulate a strategy that effectively addresses the problem. Emphasis is placed on the microsurgery of nerve topics: direct nerve repair, autogenous cable nerve grafting, biodegradable conduits, decellularized nerve allograft, and transfer of the anterior interosseous nerve to the ulnar motor branch. The discussion covers the relationship between choices made at the level of the original injury at the cubital tunnel to the timing and selection of distal reconstructive efforts, with specific attention to the distinction between end-to-end anterior interosseous to ulnar motor branch transfer as opposed to the supercharged end-to-side variation of this procedure.
Keywords: Grafting; Laceration; Nerve; Release; Ulnar